PERAN MAHASISWA DALAM MEMBANGUN INTENSITAS LEMBAGA TPQ MAZIDATUL KHOIR YANG MODERN: PERAN MAHASISWA DALAM MEMBANGUN INTENSITAS LEMBAGA TPQ MAZIDATUL KHOIR YANG MODERN - viqhy muhammad alwi viqhy masroeri; Vellyna Dwi Setyaningrum; Alvika Tanzila Azizatul Zara; Syarifah Devla Fifiatillah Arzabeit; Nur Cholifah (PPM LP2M UIN Alauddin Makassar, 2023)
Abstrak : This research was conducted using qualitative research methods. Descriptive analysis techniques for class action research. By using 4 stages namely: Planning (Planning), Implementation of Action (Action), Observation (Observing), Reflection (Reflection). This research aims to explain the importance of the existence of TPQ mazidatul khoir and the innovations / new breakthroughs provided by students of KKM Uin Malang in the form of extracurricular programs such as the tahfidz program, the Pegon script program, the Pildacil program, the Madhrasah Diniyah program, with the aim of increasing the competence of children's skills so that can give birth to a young generation of qualified Qur'ani. Keywords: tpq mazidatul khoir, extracurricular programs, student roles, KKM, ganendra